Strategic Foresight Accelerating Technological Change - Cheah, Sarah Lai-Yin (De Gruyter, 2020)
Strategic foresight is discipline that organizations adopt to gather, interpret, manage information about the future environment they plan to operate in. This book introduces the concept of strategic foresight and advocates a holistic and systemic foresight approach comprising five phases that are suitable for organizations in the public and private sectors. Using real-life cases as practical examples, the book demonstrates how organizations can apply a range of foresight methods and resources across the phases from intelligence to implementation. The book offers an opportunity to learn by all key stakeholders. It enhances the understanding of the National Research Organization's Foresight exercise (as the complex social phenomenon) in its context. The case study of the National Research Organisation provides lessons and insights that can improve both the theoretical and practical implementation of the Foresight Exercise.Dr Mlungisi CeleActing Head: National Advisory Council on InnovationDepartment of Science and Technology, Republic of South Africa Foresight methodologies have been widely spreading among business and research organizations worldwide during the last decades. The weakest point of many forward-looking activities so far was the lack of their practical use. The books shows, on a number of cases, how a Foresight study, being wisely designed and implemented, can become a useful navigation tool for increasing competitiveness in the fast changing environment.